The Library as organization [soundrecording] a view from the middle - Lutz, Raymund P. (Development digest premier series, 1974)
A review of the basic organizational theory as it may apply to library management. It also presents a "state of the art" summary on library personnel administration and problems of promoting ideas to others. Ella Yates in this tape urges librarians to include lower level personnel in decision-making, planning, and executive directives.